Customização de ambientes virtuais de orientação e mobilidade para pessoas com deficiência visual - Façanha, Agebson Rocha (2021)
People who are blind find greater barriers in performing tasks that require spatial representation. Thus, the absence of vision can create difficulties for the individual to discern their current location, establish the position of other people or objects in physical space, set the direction to go and reach the desired destination. These are some of the problems faced daily by visually impaired people, and any information gained about the surrounding characteristics tends to be significant and relevant to decision making regarding moving actions. The organization of this information and the choices made are directly involved in improving cognitive processes, which are responsible for storing, retrieving and decoding information about the location and specific attributes of a physical space, which may lead to greater autonomy in its mobility. For this reason, the construction of mental maps is an important skill for these individuals and can occur through direct contact with the environment, or with the help of descriptive or verbal maps, or even with the support of technology. This thesis reports the research and development process of an indoor navigation audio-haptic map editor. Differently, from other works that provide solutions specific to a given environment, the proposed system will allow orientation and mobility teachers to create the maps to be used in their practical classes with the visually impaired learners, thus favoring the autonomy of these subjects. In addition to the development of the map editor, this work proposes a model, implements an O&M environment for mobile devices, and assesses its usability with 25 specialists in human-computer interaction, 24 guidance and mobility teachers, and 10 people with disabilities visual. These steps seek a better understanding of their applicability in improving the navigation and wayfinding of people with visual impairments to make them more autonomous and independent in their relationships with others, objects, and environments.